SUONA TEACHING AND RESEARCH IN MUSIC UNIVERSITY - Xin, Liang; Taipanich, Chinnapat (Asia Pacific Journal of Religions and Cultures, 2025)
This article examines the curriculum, instructional methods, and cultural significance of Suona education in Chinese music universities, with a focus on Shenyang institutions. Suona instruction is structured to develop students’ performance skills, teaching abilities, and cultural awareness, thereby preserving and promoting traditional Chinese music. This wind instrument, integral to China’s cultural, spiritual, and religious heritage, is historically associated with community rituals, celebrations, and religious ceremonies. The article explores how Suona education intertwines with these traditions, fostering cultural confidence and reinforcing the social and spiritual values embedded in Chinese music. By integrating traditional teacher-apprentice approaches with modern multimedia and virtual methods, universities create a well-rounded educational experience. This approach not only equips students for professional roles in music but also strengthens Suona’s role as a cultural symbol and artistic legacy in modern China, emphasizing its continuing importance in cultural preservation and identity. This article presented (1) Suona teaching in music university, (2) research in Suona teaching.